Unlocking Local Prosperity: Empowering Communities through Small Business Financing - MY, Nurfadila (Golden Ratio of Community Services and Dedication, 2023)
This study aims to investigate the role of small business financing in promoting community empowerment and local prosperity. Employing a qualitative research methodology, the study conducts a comprehensive literature review to explore the economic, social, and environmental dimensions of small business financing. The research design involves systematic data collection from diverse sources, including academic journals, books, reports, and online databases, followed by thematic analysis to identify key insights and patterns within the literature. The findings underscore the pivotal role of small businesses as drivers of economic growth, social cohesion, and environmental sustainability within local communities. Despite the significant contributions of small businesses, various systemic challenges hinder access to finance, particularly for marginalized groups. Innovative financing mechanisms, such as microfinance initiatives and impact investing, emerge as promising strategies to address the financing gap and promote inclusive growth. The study concludes by emphasizing the importance of holistic approaches to SME development and community empowerment, urging policymakers and practitioners to prioritize financial inclusion, sustainable business practices, and interdisciplinary collaboration.